Economic analysis of integrated vegetable and poultry production systems in the Babati District of Tanzania - Naphtal, H. (University of Bonn, 2018)
Attaining food security remains a global challenge as the supply of sufficient quantity and nutritious food is threatened partly due to climate change, high cost of production and rapid growing population. Recently, vegetables and poultry production have attracted attention both from the scientific and policy making communities for their contribution to food security as well as the opportunities they offer in improving the livelihood of smallholder farmers. Despite the efforts made, the profitability of vegetable-poultry (V-P) integration system is yet well-known, particularly in Tanzania. This study therefore, employed the Gross Margin (GM) analysis to evaluate the profitability of V-P integration and logit model to determine factors influencing adoption of V-P integration farming system using a cross-sectional data collected from 250 households in Babati District, Tanzania. The findings show that vegetable-poultry integration is more profitable than vegetable farming alone and the profitability increases as the flock size increases. Moreover, for smallholder farmers to make significant profits from V-P production system, they should keep at least 18 chickens per household. The decision to integrate V-P production systems is influenced by gender, education level and marital status of the head of the household, household size, off-farm income, land owned, total income received by the household, and awareness of V-P integration benefits. The policy implication is that scaling up promotion of the vegetable poultry production practices and adoption of new farming technologies are essential for efficient utilization of available resources and increase the profitability of V-P integration system. This can be done through farmers’ capacity building, increased provision of trainings and extension services which contribute in transforming the rural farming from subsistence to profit-oriented farming.